Investigation on Aromaticity Index and Double-Bond Equivalent of Aromatic Compounds and Ionic Liquids for Fuel Desulphurization - Syamsul B. Abdullah; Z. Man; M. A. Bustam (Journal of Chemistry)
Aromaticity index (AI) and double-bond equivalent (DBE) were studied to seek a simpler approach in identifying suitable ionic liquids for the desulphurization process. Manifestation of interaction mechanism by COSMO-RS and Raman spectroscopy is discussed. The findings demonstrate that AI and DBE calculations can be used to analyze and arrogate potential combination of cation and anion for fuel desulphurization purposes.